IMPLEMENTATION OF GOOD SCHOOL GOVERNANCE IN BUILDING SCHOOL CULTURE WITH CHARACTER AT MAN 2 PONTIANAK - Rizky I'malia Sari; Wahyudi Wahyudi; Usman Radiana (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
This study aims to describe the implementation of good school governance in building a school culture with character at MAN 2 Pontianak. The research method used is descriptive analysis with a qualitative approach. Data was collected by using the observation, interview, and documentation techniques. The subject of this research is based on purposive sampling. The results of this study have shown that the principles of good school governance play an important role in building a school culture with character by applying the principles of good governance, viz participation, transparency and accountability in every school activity. This is reflected in the vision, mission, goals, school program and efforts to realize it. The conclusion of this study is the principle of good governance that is oriented to the needs of schools and communities would create an involvement, interaction, trust, and commitment to jointly realize akhlakul karimah as a educational goals which is carried out through planting, habituating, exemplary and leadership to integrate character values continously in every school activity. So that the culture of character becomes the basis of a person's behavior that triggers a balance between IQ, SQ, and EQ of the school elements.